(untitled) (Journal of the College of Basic Education, 2025)
The aim of the research is to identify the effect of the selective thinking model on the curiosity of fourth-grade primary school students towards mathematics. The experimental research method was followed to achieve the research goal. The research sample was chosen intentionally and consisted of (105) male and female students from the fourth-grade primary school students at (Sabaa Mixed Elementary School), for the second semester of the academic year (2024-2025 AD). By random selection of the classes, Class (B) was chosen to be the experimental group that studied according to the selective thinking model with (51) male and female students, consisting of (24) male students and (27) female students, and Class (A) was chosen to be the control group that studied according to the usual method with (54) male and female students, consisting of (30) male students and (24) female students. The two groups were rewarded in the following variables (chronological age in months, intelligence and previous knowledge in mathematics, previous achievement For the mathematics subject and the educational level of the parents, the research tool was constructed, consisting of a cognitive curiosity test (formal), which included (20) items, and a cognitive curiosity scale (verbal), which included (20) items. Their validity was confirmed using the Kuder-Richardson equation (KR-20). The reliability coefficient of the (formal) curiosity test was (0.83), and using the (Cronbach’s alpha) equation, the reliability of the cognitive curiosity scale (verbal) items was (0.85) After completing the experiment, the curiosity test and scale were applied to the two research groups. Using the statistical program (spss), the results showed the presence of statistically significant differences at the significance level (0.05) between the average scores of the students in the experimental group and the scores of the students in the control group in the curiosity test and scale, in favor of the experimental group according to the teaching method. In light of the research results, a number of conclusions, recommendations, and proposals were reached.